Cails paper wash / Aisyah Nur Izzah Azhar ... [et al.] - Azhar, Aisyah Nur Izzah; Mohd Jaffri, Intan Nafissa; Noh, Loris; Kiroh, Caroline; Kibat, Silverina Anabelle (2021)
The Transportation Security Administration (TSA) has restricted liquids in carry-on bags on all airlines to travel-sized containers weighing 3.4 ounces (100 milliliters) or less per item. Apart from the security reasons stated by the TSA on their website, it is widely known that liquids require very good and proper packaging, especially when traveling by plane. With all of these constraints, Cails Paper Wash was created to cut down on the time spent preparing all of the essentials that any traveler requires. Cails Paper Wash is an organic sheets face wash that will save the traveler not only time but also money by reducing the chance of spilled liquid, which is normally messy because it contaminates other products in the same bag. The fact that Cails paper wash is made of paper would also help to minimize the weight and space taken up by liquid products that are usually packaged in larger containers. The key ingredients of paper, distilled water, oatmeal extract, and vegetable glycerin. It is also suitable for all skin types because the main ingredient is vegetable glycerin, which has a smooth reaction to all skin types and reduces inflammation. Cails Paper Wash is simple to use - just take one sheet, place it on your palm, add some water, rub it in gently, and begin foaming. The user then only needs to gently massage it onto their face before rinsing it away. Cails Paper Wash is seen as having a high potential for commercialization due to its comfortability, low cost, and packaging value. This product was developed with two objectives in mind: to reduce the dilemma of carrying a small amount of liquid on board, and to make the product a solution to any traveler's packaging concern.